INOVASI PENGEMBANGAN ASESMEN KOMPETENSI MINIMUM (AKM) LEVEL 1 BERBASIS LITERASI DAN NUMERASI - Acesta, Arrofa; Isnaini Wulandari; Ndaru Mukti Oktaviani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to: (1) develop a feasible Minimum Competency Assessment (AKM) instrument for Level 1 to be used in Grades I and II at SD Negeri 2 Citenjo, Kuningan, West Java, and (2) evaluate the effectiveness of the instrument in supporting learning in Grades I and II. This research employs a development method (Research and Development/R&D) based on the Borg and Gall development model, which consists of three main stages: (1) preliminary study, (2) development, and (3) testing and implementation. The preliminary testing subjects consisted of two expert validators, while the main testing subjects included 21 second-grade students. Data collection instruments included interview guidelines, AKM instrument evaluation questionnaires by expert validators (curriculum 2013 experts and evaluation instrument experts), and teacher response questionnaires to the product. Data analysis utilized Aiken’s V statistical technique to assess validity during the limited trial, while product effectiveness was tested through student test results. Item quality analysis included difficulty level, item discrimination, and reliability testing. The research results indicate that during the limited trial stage, the Level 1 AKM instrument was deemed highly feasible, with an average Aiken’s V score of 0.862, reflecting very high validity. Effectiveness testing showed that the Level 1 AKM instrument could accurately measure students' literacy and numeracy skills across four competency categories. In terms of item quality, the AKM instrument demonstrated good item discrimination and a proportional difficulty level to reflect students' literacy and numeracy abilities. Reliability testing yielded excellent results, with a range of 0.96 for literacy components and 0.94 for numeracy components.